Undergraduate Nursing Students' Knowledge and Attitudes Towards Dementia: A Cross-Sectional Study in Iraq: Pengetahuan dan Sikap Mahasiswa Keperawatan terhadap Demensia: Sebuah Studi Cross-Sectional di Irak - Hammooz, Asmaa (Universitas Muhammadiyah Sidoarjo, 2025)
Background: A reduction in cognitive function, or the ability to think, is typically the outcome of dementia, a disorder that can be caused by a number of diseases that progressively harm the brain and break down nerve cells. Objectives: to evaluate the student's knowledge and attitude regarding dementia and to determine the connection between students' demographic traits and their knowledge and attitude. Methods: Undergraduate nursing students participated in a descriptive cross-sectional study. Nonprobability purposive sampling was chosen for (264) students in the College of Nursing University of al-Qadisiyah. In order to engage in the study, the researcher uses an instrument that is divided into three parts: part one is a demographic data form; part two includes information about dementia form includes (30) items, and part three is attitude toward dementia form (9) items. Results: According to the study's findings, students' overall knowledge rating was fair, with a mean score of 0.58. Conclusion: As the student progresses through the academic stages, their knowledge increases and this knowledge is reflected in their attitudes towards dementia, the study showed that the knowledge of the student in the fourth class with, and in the attitudes. Highlights: Dementia reduces cognitive function due to brain cell damage. Assess nursing students’ dementia knowledge, attitude, and demographic influence. Cross-sectional study of 264 students using structured questionnaires. Keywords: Undergraduate Nursing student, dementia, knowledge, attitude.